A case report of pulmonary tritrichomonosis in a pig - Yuanyuan Shi; Wei Jiang; Zhiyong Ma; Yafeng Qiu (BMC Veterinary Research, 2017)
Abstract Background Tritrichomonads like porcine Tritrichomonas foetus (previously named Tritrichomonas suis), can commensally live in nasal cavity of pigs, but it is rare to cause pulmonary tritrichomonosis. Case presentation A 40-day-old piglet was presented for persistent labor breathing and diagnosed with parasite infections in the lung by analysis of bronchoalveolar lavage (BAL) under microscope. By taking advantage of next-generation sequencing approach, we found 9611 homologous tags belonging to 50 annotated genes of tritrichomonads by analysis of mRNA of the bronchoalveolar lavage with the parasite infection. Furthermore, RT-PCR and DNA sequencing analysis confirmed the presence of the tritrichomonad. Findings Here, we report a case of pulmonary tritrichomonosis in a pig. By taking advantage of next-generation sequencing approach, we found 9611 homologous tags belonging to 50 annotated genes of tritrichomonads by analysis of mRNA of the bronchoalveolar lavage with the parasite infections. Furthermore, RT-PCR and DNA sequencing analysis confirmed the presence of the tritrichomonad. Conclusion Our results demonstrate that tritrichomonads like porcine Tritrichomonas foetus can cause lung infections of pigs and reveal that next-generation sequencing is potential to identify rare diseases like pulmonary tritrichomonosis in clinical.